Rancang Bangun Aplikasi Sandi Semaphore pada Perangkat Mobile berbasis Android - Rangga Firdaus; Machudor Yusman; Tangguh Pramono (Jurnal Komputasi, 2014)
Semaphore is a medium to communicate from one person to another. The process of studying semaphore codes is quite difficult and requires a relatively long time because of the limited medium for learning this code. This research aims to design and develop the application for learning semaphore code on Android-based mobile devices as well as providing an alternative learning media for semaphore code learners. Android mobile devices selected as the basis of application development considering of the use of those Android technologies.This application was developed with the Java, HTML, CSS and JavaScript programming language. The data used are motion pictures semaphore. The application tests was carried out using the Blackbox Testing method. The testing is done by examining the functional features of the application. The test results of system and application test shows that the Semaphore Code Application is able to run well on Android operating system applied on Ice Cream Sandwich and Jelly Bean version and also able to translate words and sentences in roman letters into motion pictures semaphores.Keywords: Android, learning media, mobile devices, semaphore.